Study on the Influence of Water Color on Signal Directionality in Laser-Induced Acoustic Processes - Tongchang Zhang; Xiaolong Cao; Qi Tan; Yiguang Yang; Yuchen Du; Jiaqi Yuan; Tengyuan Cui; Jianquan Yao (Journal of Marine Science and Engineering)
Implementing information encoding in laser acoustic signals by altering the medium’s color is one of the current hot research topics. Modulating the color of the medium can modulate the directionality of laser acoustic signals; however, there has been little research on the impact of water color on laser acoustic signals. This paper investigates the relationship between the directionality of laser acoustic signals and water color, innovatively proposing a conical sound source model. It points out that the ratio of the model’s radius (r) to the model’s vertical line (d) is a decisive factor affecting directionality. Through simulations and experiments, it has been verified that laser acoustic signals exhibit no significant directionality (r/d = 10) and that the energy distribution of sound signals in the vertical direction significantly decreases (r/d = 0.4). Sound signal directivity and absorption rate were studied in the environment of red, blue, and yellow water, and the time–frequency characteristics were also studied. The acoustic signals produced by laser breakdown of different colors have obvious time–frequency characteristic differences, among which the signal intensity generated by laser incident on yellow water is 180.13 dB and the signal intensity generated by laser incident on black water is 168.31 dB. The peak frequency of sound signal generated by laser breakdown of yellow water is the highest, which is 21,240 Hz, and the peak frequency of sound signal generated by laser breakdown of water is the lowest, which is 8828 Hz. There is an obvious positive correlation between the peak frequency of sound signals and the laser absorption rate, and calculation of the optimal water color corresponding to the highest detection threshold at different distances provides guidance for the application of laser acoustic communication.